Financial Management: Fundamental Factors Against Stock Prices on the Indonesia Stock Exchange - Marjohan, Masno (JURNAL BISNIS STRATEGI, 2024)
This study aims to analyze internal fundamental factors that affect the share prices of consumer industry companies listed on the Indonesia Stock Exchange against stock prices for the period 2013 – 2022. The population in this study is annual financial statements, while the samples used are balance sheets, financial statements, income statements, financial statements, and other reports for the last 10 years. The methods used are multiple linear regression test analysis, coefficient of determination, partial t- test, and simultaneous F test, using SPSS. The results showed that the adjustment value of the R square coefficient of determination was 0.874, which means that the independent variable affects the dependent variable by 87.4% and the remaining 12.6% is influenced by other variables outside this study. The results of Test F prove that there is a simultaneous influence of fundamental factors on Stock Price, while the results of Test t prove that some fundamental factors on Stock Price have no effect. The recommendation for the next researcher is to add variables, the scope of research is further expanded, and for investors to pay attention to the stock price and value of the Company.